Developmental Changes in Expression of βIV Spectrin Splice Variants at Axon Initial Segments and Nodes of Ranvier - Yoshimura, Takeshi; Stevens, Sharon R.; Leterrier, Christophe; Stankewich, Michael C.; Rasband, Matthew N. (Frontiers in Cellular Neuroscience, 2017)
Axon initial segments (AIS) and nodes of Ranvier are highly specialized axonal membrane domains enriched in Na+ channels. These Na+ channel clusters play essential roles in action potential initiation and propagation. AIS and nodal Na+ channel complexes are linked to the actin cytoskeleton through βIV spectrin. However, neuronal βIV spectrin exists as two main splice variants: a longer βIVΣ1 variant with canonical N-terminal actin and αII spectrin-binding domains, and a shorter βIVΣ6 variant lacking these domains. Here, we show that the predominant neuronal βIV spectrin splice variant detected in the developing brain switches from βIVΣ1 to βIVΣ6, and that this switch is correlated with expression changes in ankyrinG (ankG) splice variants. We show that βIVΣ1 is the predominant splice variant at nascent and developing AIS and nodes of Ranvier, but with increasing age and in adults βIVΣ6 becomes the main splice variant. Remarkably, super-resolution microscopy revealed that the spacing of spectrin tetramers between actin rings remains unchanged, but that shorter spectrin tetramers may also be present. Thus, during development βIV spectrin may undergo a switch in the splice variants found at AIS and nodes of Ranvier.